PENGARUH PENAMBAHAN UBI JALAR UNGU TERHADAP SIFAT ORGANOLEPTIK ES KRIM SUSU KAMBING PERANAKAN ETAWA [The Influence of Purple Sweet Potato Increment og Organoleptic Characteristic of Goat Milk Ice Cream of Etawa Generation] - Susilawati Susilawati; Fibra Nurainy; Aditya Wahyu Nugraha (Jurnal Teknologi & Industri Hasil Pertanian, 2014)
Goat milk is perishable foodstuffs and has  low shelf life. One way to preserve it is process goat milk into ice cream. This is usefulforreducingthe damagenutritiongoat milk. Purple sweet potatoes which contain some anthosianin can be added to inprove the texture. However, the amount of purple sweet potato  added will affect the texture and body of icecream.  Therfore this research is needed. This research was purposed to find concentration of purple sweet potato that will produce the best ice cream especially on organoleptic characteristic. The experiment was arranged in  Latin Square design in single factor that consist of 5 levels  concentrations of purple sweet potato paste. There were 0% (reference), 10%, 20%, 30%, and 40% (b/b) with 5 replications. Data were analyzed using analysis of variance . furtehre tested using the HSD Test in 5% level of signiificance. The The results showed that addition of  30%  sweet potato paste produced the best quality of goat milk ice cream of Etawa . The score of aroma was 3,5 (not specific goat milk), the taste’s score was 3,47 (sweet), color’s score was 2,8 (rather purple), texture’s score was 3,5 (soft), and the overall  of acceptance was 3,203 (rather like). This ice cream contained water, protein, fat, ash, crude fiber, and total carbohidrate as amuch as 66,98%, protein was 5,5%, 11,86%, 1,34%, 0,3% and 14,2%. Keyword : goat milk, ice cream, purple sweet potato